Occupational therapy without borders : integrating justice with practice - Sakellariou, Dikaios; Pollard, Nick (Elsevier, 2017)
The new edition of this landmark international work builds on the previous two volumes, offering a window onto occupational therapy practice, theory and ideas in different cultures and geographies. It emphasizes the importance of critically deconstructing and engaging with the broader context of occupation, particularly around how occupational injustices are shaped through political, economic and historical factors. Centering on the wider social and political aspects of occupation and occupation-based practices, this textbook aims to inspire occupational therapy students and practitioners to include transformational elements into their practice. It also illustrates how occupational therapists from all over the world can affect positive changes by engaging with political and historical contexts. Divided into six sections, the new edition begins by analyzing the key concepts outlined throughout, along with an overview on the importance and practicalities of monitoring and evaluation in community projects. Section Two explores occupation and justice emphasizing that issues of occupational injustice are present everywhere, in different forms: from clinical settings to community-based rehabilitation. Section Three covers the enactment of different Occupational Therapies with a focus on the multiplicity of occupational therapy from the intimately personal to the broadly political. Section Four engages with the broader context of occupational therapy from the political to the financial. The chapters in this section highlight the recent financial crisis and the impact it has had on people’s everyday life. Section Five collects a range of different approaches to working to enable a notion of occupational justice. Featuring chapters from across the globe, Section Six concludes by highlighting the importance and diversity of educational practices.